Clinical value of plasma hsa_circ_005230 in the diagnosis and prognosis evaluation of primary hepatocellular carcinoma - Yimamaimaitijiang·ABRA, Pakhardin·BAIKERE, YI Chao, TONG Qing (Jichu yixue yu linchuang, 2023)
Objective To detect the expression level of circular RNA (circRNA) hsa_circ_005230 in the plasma of primary hepatocellular carcinoma (HCC), and to explore its clinical value in the diagnosis and prognosis of HCC. Methods The non-coding RNA high-throughput sequencing data in the GEO database was used to screen the circRNA expression in HCC (cancer tissue/paracancerous tissue). RT-qPCR was used to detect hsa_circ_005230 in the plasma of 60 HCC patients, 30 hepatitis B patients and 30 healthy people. Expression levels and their relationship with clinicopathological characteristics of HCC patients were evaluated. The receiver operating characteristic(ROC) curve to evaluate the clinical value of hsa_circ_005230 in the diagnosis of HCC. Survival analysis was performed by Kaplan-Meier method, and multivariate prognostic analysis was performed by Cox regression. Results The most significant up-regulated expression was found in hsa_circ_005230 from the GEO database. The expression level of hsa_circ_005230 in plasma of HCC patients was significantly higher than that of hepatitis B group and healthy control group (P＜0.01); The increase of hsa_circ_005230 expression was related to tumor size (P＜0.05) and to the stage of tumor lymph node metastasis(P＜0.01); ROC analysis showed that the area under the ROC curve (AUC) of plasma hsa_circ_005230 in differentiating HCC from healthy people was 0.69, the sensitivity was 70%,and the specificity was 82 %.The overall survival rate of patients with high hsa_circ_005230 level was significantly lower than that of patients with low hsa_circ_005230 level. Univariate analysis showed that alpa-fetoprotein(AFP)(P＜0.01) and hsa_circ_005230 (P＜0.01) were related factors affecting the prognosis of HCC. Cox multivariate analysis revealed that hsa_circ_005230 was an independent prognostic indicator in HCC patients. Conclusions The hsa_circ_005230 may be used as a new biological marker for the diagnosis and prognostic evaluation of HCC.